A study of clinical and etiological profile of mitral valve dysfunction - B., Prashanth; Pauskar, Mahendra M.; Managuli, Mahesh; K., Vijayalaxmi (International Journal of Research in Medical Sciences, 2024)
Background: Heart valve diseases are a leading cause of cardiovascular morbidity and mortality globally; putting a significant strain on healthcare resources. In developing countries, rheumatic heart disease (RHD) remains the most common type of heart valve disease. Mitral valve disease is the most frequent of the valvular heart diseases. Mitral valve disease is a distressing and painful condition, and requires immediate attention before they result in death. Methods: This was a prospective observational study done from September 2019 to February 2021, at the Department of General Medicine, Goa Medical College and Hospital, Bambolim, Goa: A tertiary care hospital in Goa. Results: Out of the 50 patients enrolled in the study 44% patients had MS ,18% had MR and 38%had MR+MS. Mean age of the study population was 41 to 50 years of which 54% patients were females. All isolated Mitral Stenosis patients were rheumatic origin. Of the 9 MR patients, predominant form of MR was ischemic (66.66%), followed by rheumatic (22.22%) and MVP (11.11%). 19 patients had MR+MS, predominant form was rheumatic (84.21%). It was also observed that 42% each of total patients had pulmonary hypertension and congestive cardiac failure, 40% had pulmonary edema, while 30% had atrial fibrillations complications. Conclusions: Our study revealed that the most common valve dysfunction observed is mitral stenosis, with a female preponderance and its most common etiology being rheumatic. Further it was also observed that the most common complication is pulmonary hypertension and congestive cardiac failure.